Comparative Evaluation of Iodine-125 Radioactive Seed Localization and Wire Localization for Resection of Breast Lesions. Issue 4 (November 2017) - Tran, Vi Thuy; David, Julie; Patocskai, Erica; Zummo-Soucy, Mathieu; Younan, Rami; Lalonde, Lucie; Labelle, Maude; El Khoury, Mona; Robidoux, André; Trop, Isabelle
Purpose: Radioactive seed localization (RSL) uses a titanium seed labeled with iodine-125 energy for surgery of nonpalpable breast lesions. RSL facilitates radiology–surgery scheduling and allows for improved oncoplasty compared with wire localization (WL). The purpose of this work was to compare the 2 techniques. Methods: We performed a retrospective study of all breast lesions operated with RSL between February 2013 and March 2015 at our university institution, and compared with an equivalent number of surgeries performed with a single WL. Imaging and pathology reports were reviewed for information on guidance mode, accuracy of targeting, nature of excised lesion, size and volume of surgical specimen, status of margins, and reinterventions. Results: A total of 254 lesions (247 women) were excised with RSL and compared with 257 lesions (244 women) whose surgery was guided by WL. Both groups were comparable in lesion pathology, guidance mode for RSL or WL positioning, and accuracy of targeting (98% correct). Mean delay between biopsy and surgery was 84 days for RSL versus 103 after WL ( P = .04). No differences were noted after RSL or WL for surgical specimen mean weight, largest diameter, and volume excised. For malignancies, the rate of positive margins was comparable (2.8%-3%), with 5 of 10 women in the RSL group who underwent a second surgery displaying residual malignancy compared with 3 of 9 women in the WL group. Conclusions: RSL is safe and accurate, and has comparable surgical endpoints to WL. Because RSL offers flexible scheduling and facilitated oncoplasty, RSL may replace WL for resection of nonpalpable single breast lesions.